2001
DOI: 10.1080/026404101317108444
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of the personal experience of the 'yips' in cricketers

Abstract: The 'yips' is a phenomenon that affects individuals who perform finely controlled motor skills. The result is involuntary movements that occur throughout the execution of a skill. A qualitative study was conducted to identify the psychological characteristics of the 'yips' experience in cricket bowlers. Eight bowlers of varying ability were interviewed about their thoughts, emotions and feelings before, during and after their initial experience of the 'yips'. After the interviews, inductive content analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 1 publication
0
67
1
4
Order By: Relevance
“…Although the yips seems to be a general phenomenon in sports (e.g. in cricket, darts, and golf; Bawden & Maynard, 2001) and studying it could lead to a better understanding of motor control and human movement, it has received relatively little attention in research. The primary focus of previous research was on the yips in golf (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although the yips seems to be a general phenomenon in sports (e.g. in cricket, darts, and golf; Bawden & Maynard, 2001) and studying it could lead to a better understanding of motor control and human movement, it has received relatively little attention in research. The primary focus of previous research was on the yips in golf (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…and Maynard (2001) found that psychologically significant sport-related events (e.g., dropped catch, embarrassment, arguments) occurred immediately prior to the first yips experience in cricket bowlers. Day et al (2006) also suggested that LMS was equivalent to a traumatic experience and might therefore trigger comparable behavioral responses to those of trauma victims.…”
Section: Aq3mentioning
confidence: 99%
“…In their study of 'yips'-affected cricketers, 374 Bawden and Maynard (2001) found that significant sport-related events (e.g., arguments with 375 teammates, a dropped catch, first game for a new team) occurred immediately prior to the onset of 376 the first experience of the 'yips'. Similarly, more recent research by Rotheram et al (2006) has 377 found that 'yips'-affected individuals often report the occurrence of major life events (e.g., death of 378 parent, relationship breakdown, moving house) prior to the initial onset of the 'yips'.…”
Section: Main Analysis 273mentioning
confidence: 99%
“…Once surveys were completed, 230 responses were scrutinized in order to ensure that only individuals who actually suffered from the 231 'yips' were entered into the database. More specifically, responses were examined for the 232 occurrence of at least one of the following criteria (chosen on the basis of previous 'yips' research, 233 e.g., Bawden & Maynard, 2001;Smith et al, 2003): an inability to perform a certain part of the 234 sport that could previously be performed with ease; an extreme fear of performing; an extreme lack 235 of control over the skill being performed; a long term movement problem; and the experience of a 236 jerk, tremor, twitch or trembling. Thirty-five participants who had completed the survey failed to 237 report at least of one these characteristics, and so Rotheram et al deemed that these individuals 238 were suffering from a poor performance, and did not have the 'yips'.…”
mentioning
confidence: 99%